Gelehrte, Ausgräber und Kunsthändler. Die Korrespondenz des Instituto di Corrispondenza Archeologica als Wissensquelle und Netzwerkindikator. Die Arbeiten der Jahre 2017 und 2018 - Thänert, Sabine; Unger, Marina (e-Forschungsberichte des DAI, 2019)
The aim of the 1829 founded explicit international Instituto di Corrispondenza Archeologica was to collect and to publish archaeological discoveries and new artifacts. A Europe-ranging network of correspondents reported from their respective territories and collections. These autographs are on the one hand all-important sources of archaeological knowledge; on the other hand, they are witnesses of the dense network formed around the Institute. The already indexed and digitized part of the letters is made available online in open access for the research community while the digital data is being elaborated using network and text-based analyses in order to visualize the network.